Facile preparation of MXene-decorated wood with excellent electromagnetic interference shielding performance. (February 2022) - Wei, Yuyi; Liang, Dandan; Zhou, Hongyang; Huang, Shoujie; Zhang, Weiwei; Gu, Jin; Hu, Chuanshuang; Lin, Xiuyi
Graphical abstract: Abstract: Wood is a promising substrate to decorate conductive material for preparing sustainable composites with electromagnetic interference (EMI) shielding function. Understanding the influences of the assembly manner of conductive materials on the EMI shielding property is essential to develop a facile fabrication method. Herein, the assembly manner of the MXene on wood is adjusted by applying three coating methods, i.e., vacuum-assisted immersion, spray coating, and brush coating. The surface morphologies, interaction between wood and MXene, electrical properties, and EMI shielding effectiveness (SE) of MXene-decorated wood (M/wood) composites were studied systematically. The results show that brush coating provides a flat and laminated MXene layer, hence an efficient conductive network can be constructed with a small loading of MXene. Ultimately, the M/wood composite prepared by brush coating displays an EMI SE of 40.5 dB at 8.2 ∼ 12.4 GHz with a MXene loading of 1.41 mg/cm 2 . Moreover, M/wood composites demonstrated excellent anti-mold function thanks to the reducing activity and fluorine-containing groups of MXene.